Financing of cultural projects through crowdfunding platforms in Poland using the example of wspieramkulture.pl - Kędzierska- Szczepaniak, Angelika; Próchniak, Joanna (Management Sciences, 2018)
Culture financing is becoming particularly important due to the growing global demand for funds in culture, even as financial institutions attitudes to such financing become more prudent. One method of obtaining funds is by using crowdfunding platforms whose role is not limited to merely raising capital, but also to creating demand or interest among stakeholders of cultural projects. Social support for culture is growing rapidly in the United States and gradually in the EU. The analysis of the market of culture crowdfunding platforms in Europe allows researchers to formulate some conclusions on projects, support attitudes and follow market trends. Crowdfunding can be an opportunity to implement many cultural projects and verify support for them
Management Sciences, 2018, vol. 23, no. 3, s. 12-22
Keywords: cultural projects; cultural sectors; cultural industries; crowdfunding; social funding; projekty kulturalne; przemysł kultury; przemysły kreatywne; finansowanie społecznościowe